Electric vehicle battery parameter identification and SOC observability analysis: NiMH and Li‐S case studies. Issue 11 (27th July 2017) - Fotouhi, Abbas; Auger, Daniel J.; Propp, Karsten; Longo, Stefano
Abstract : In this study, battery model identification is performed to be applied in electric vehicle battery management systems. Two case studies are investigated: nickel‐metal hydride (NiMH), which is a mature battery technology, and lithium‐sulfur (Li‐S), a promising next‐generation technology. Equivalent circuit battery model parameterization is performed in both cases using the Prediction‐Error Minimization algorithm applied to experimental data. Performance of the Li‐S cell is also tested based on urban dynamometer driving schedule (UDDS). The identification results are then validated against the exact values of the battery parameters. The use of identified parameters for battery state‐of‐charge (SOC) estimation is also discussed. It is demonstrated that the set of parameters changes with a different battery chemistry. In the case of NiMH, the battery open circuit voltage (OCV) is adequate for SOC estimation whereas Li‐S battery SOC estimation is more challenging due to its unique features such as flat OCV‐SOC curve. An observability analysis shows that Li‐S battery SOC is not fully observable and the existing methods might not be applicable for it. Finally, the effect of temperature on the identification results and the observability are discussed by repeating the UDDS test at 5, 10, 20, 30, 40 and 50 degree Celsius